Association of cannabis use disorder with cardiovascular diseases: A two-sample Mendelian randomization study - Chen, Miao; Lu, Yun-long; Chen, Xiao-fan; Wang, Zhen; Ma, Liang (Frontiers in Cardiovascular Medicine, 2022)
Background: The use of cannabis has increased globally due to more regions decriminalizing marijuana use for therapeutic and recreational aims. Several observational studies have revealed that cannabis use is associated with an increased risk of adverse cardiovascular pathologies and diseases. Nevertheless, the causal associations between cannabis use and cardiovascular diseases remain unclear. Hence, we performed single-variable and multivariable Mendelian randomization (MR) to evaluate the association between cannabis use disorder and various cardiovascular diseases. Methods: Summary statistics were collected from the largest-to-date genome-wide association studies (GWAS) of cannabis use disorder. The 12 SNPs for cannabis use disorder were used as instrumental variables in this study. MR estimates were pooled using a random-effects inverse-variance weighted (IVW) method. Simple median and weighted median methods were conducted as sensitivity analyses. Results: The genetic liability to cannabis use disorder was associated with an augmented risk of coronary artery disease, myocardial infarction, atrial fibrillation, heart failure, deep venous thrombosis, pulmonary embolism, and stroke. Except for stroke, the results were inconsistent in the sensitivity analyses. The overall patterns for the associations of cannabis use disorder with atrial fibrillation, heart failure, pulmonary embolism and stroke remained in multivariable MR analyses adjusting for potential mediators, including smoking, alcohol, body mass index, blood lipid, type 2 diabetes, hypertension, and depression. However, the association with coronary artery disease, myocardial infarction, and deep venous thrombosis did not persist in multivariable MR analyses. Mediation analysis demonstrated that smoking, body mass index, low-density lipoprotein, hypertension, and depression have more significant mediation effects, which suggests that these factors partly mediate the link from cannabis use disorder to coronary artery disease, myocardial infarction, and deep venous thrombosis. Conclusion: The genetic liability to cannabis use disorder was associated with a higher risk of atrial fibrillation, heart failure, pulmonary embolism, and stroke. The evidence for the association between cannabis use disorder, coronary artery disease, myocardial infarction, and deep venous thrombosis was weak. Hence, future use of cannabis for therapeutic and recreational aims should consider its potential impact on cardiovascular diseases.